Biodiversity of Forensically Relevant Blowflies (Diptera: Calliphoridae) at the Anthropology Research Facility in Knoxville, Tennessee, USA - Yangseung Jeong; Lauren M. Weidner; Simon Pergande; Denise Gemmellaro; David E. Jennings; Krystal R. Hans (Insects, 2022)
Understanding the biodiversity and distribution of forensically relevant blowflies (Diptera: Calliphoridae) in a region can aid in legal investigations when insects are associated with remains. For this purpose, we conducted a 14-month-long blowfly survey at the Anthropology Research Facility (ARF) of the University of Tennessee in Knoxville, Tennessee. Traps baited with pork kidney were deployed for 24 h twice a month throughout the study. A total of 3180 adult blowflies were collected, comprising 13 species from 7 genera. Phormia regina (Meigen) and Lucilia coeruleiviridis (Macquart) were the predominant species collected from this survey, with collections representing 65.9% and 20.6%of total flies captured, respectively. In addition to relative abundance, we investigated blowfly community composition, species abundance, richness, and diversity by season. One state record was identified, with adult Protophormia terraenovae (Robineau-Desvoidy) being collected for the first time in Tennessee. Additionally, an earlier record of Chrysomya megacephala (Fabricius) in Tennessee was noted. These findings can be used to aid in legal investigations in the area and surrounding areas where work is limited, as well as to provide information on which forensically relevant species should be the subject of future research in the area.